Evaluation of the antifungal activity of olive leaf aqueous extracts against Candida albicans PTCC-5027 - Nasrollahi, Z (Curr Med Mycol, 2015)
In this study, antifungal property of olive leaf extracts against Candida albicans PTCC-5027 was examined. Fresh olive leaf extracts were prepared using distilled water in a Soxhlet apparatus. The antifungal activity of the extract was analyzed by measuring the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC), using the microdilution test and disc diffusion assay. The olive leaf aqueous extracts exhibited antifungal effects against the yeast with an MIC of 24 mg/ml, MFC of 48 mg/ml, and inhibition zone diameter of 21 mm. The results indicated the sensitivity of Candida albicans PTCC-5027 to olive leaf aqueous extracts.